Women food entrepreneurs in Bangladesh: a qualitative research agenda on social enterprise perceptions - A Jannat, Shetu Gull; Mohamad, Siti Fatimah; Abdul Halim Lim, Sarina (Global Academic Excellence, 2024)
In recent years, the emerging trend of female entrepreneurship as a sustainable activity has attracted the attention of developing countries such as Bangladesh. Nevertheless, the issues of entrepreneurial leadership and gender relevant to female entrepreneurship have not been sufficiently explored. The growth of social entrepreneurs in Bangladesh remains low compared to the country's population and social problems. Women entrepreneurs have demonstrated their potential to serve society by playing an increasingly important economic role, actively creating jobs and income, and contributing to the tax base. Therefore, it is important to focus on existing women entrepreneurs and their motivations for transforming their businesses into social enterprises. This study proposes an agenda to explore the perspectives of women food entrepreneurs in Bangladesh regarding the development of their food business into a social enterprise, with a focus on the potential impact on food security and sustainable growth. The research agenda emphasizes the relevance and effectiveness of women entrepreneurship in the food sector. Using a qualitative approach, the research agenda aims to gather insights from women entrepreneurs in the food sector. The findings are expected to contribute to discussions on sustainable development and women’s empowerment and highlight the role of women-led social enterprises in the food industry.